EDITORIAL NOTE - Faridah Hj. Hassan, (Asian Academy of Management Journal, 2019)
The First International Conference of the World Academy of Islamic Management with the theme, “To the Frontier of Management from Islamic Perspective” was successfully organised on 12–13 May 2018 at Bestari Hall, Universiti Kuala Lumpur (UniKL). The main objective of the conference was to share knowledge and research findings on disciplines related to Islamic management.More than 100 academic papers and 50 abstracts were received from academics and researchers from all over the world. The papers were written covering various topics and areas in Islamic management including Islamic finance and accounting, economics, Islamic marketing, Islamic management, and other disciplines. Some of these papers are good and have great potential to contribute to the body of knowledge in Islamic management.In this special issue of Asian Academy of Management Journal (AAMJ), 14 papers from the conference were selected to be published in this esteemed journal. This special issue features papers on Islamic finance, takaful, economics, education, management, and other areas relevant to Islamic management in order to portray that Islamic management covers vast areas or disciplines that should not be ignored by scholars and practitioners.Special thanks to the team of review committee who have exerted outstanding effort to ensure that the published papers meet the quality standard of the journal. The credit goes to Emeritus Professor Dr. Mohamed Sulaiman, Asssociate Professor Dr. Gholam Reza Zandi, Associate Professor Dr. Suhaimi Muhd Sarif, Associate Professor Dr. Abdul Kadir Othman, Associate Professor Dr. Saridan Abu Bakar, and Dr. Nor Azura Adzharuddin for their incessant struggle to make this happen.